Pendampingan Distribusi Bantuan Langsung Tunai Dana Desa Terhadap Keluarga Penerima Manfaat Desa Tegalsari Kecamatan Garung Kabupaten Wonosobo - Miftahudin Miftahudin; Robingun Suyud El Syam (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
In 2020 the Indonesian government implemented the Village Fund Direct Cash Assistance (BLT DD) program aimed at the poor affected by Covid-19. So it is necessary to provide assistance so that the assistance is right on target. Through the field method, the study concluded: That assistance in the distribution of direct cash assistance from village funds to beneficiary families in Tegalsari village, Garung sub-district, Wonosobo district through four strategies, namely the Determination Meeting of Beneficiary Families (KPM), KPM Data Validation, Cooperation with Banks, and BLT Distribution DD. This assistance is useful in ensuring that government assistance programs are right on target for the purpose of social welfare in Tegalsari Village.